Heteropolymetallic copper(II)-gold(III) dithiocarbamate [2]catenanes via magic ring synthesis. - Wong, W; Cookson, J; Evans, E; McInnes, E; Wolowska, J; Maher, J; Bishop, P; Beer, P (2005)
A rare class of mixed-metal [2]catenane has been assembled via magic ring synthesis of dinuclear copper(II) and gold(III) dithiocarbamate macrocycles.